HUBUNGAN INSOMNIA TERHADAP TINGKAT KONSENTRASI BELAJAR PADA REMAJA DI DESA JATI MULYA KABUPATEN TANGERANG - Mutmainatul Mardiyah; Eka Noviana Nasriyanto; Lastri Mei Winarni (Nusantara Hasana Berdikari, 2022)
Insomnia cases in Indonesia are estimated to reach 10%, which means that from a total of 238 million Indonesians, around 23 million people suffer from insomnia. The effect of insomnia on concentration a person will be sleepy during the day so that it can reduce concentration and will interfere with activities. The purposes of research: to find out the description of the relationship between insomnia on health and the level of learning concentration in adolescents, how the description of insomnia on the level of learning concentration in adolescents. This research is quantitative with a survey method using questionnaires with probability sampling technique, namely cluster sampling to determine several clusters from the results of selecting some individuals who are part of a population. The results of the Chi-square statistical test obtained a p value of 0.001 (p <0.05). There is a relationship between insomnia and the level of learning concentration in adolescents in Jati Mulya Village, Tangerang Regency which shows that the higher the insomnia in adolescents, the concentration will decrease.